Community perspective towards Eichhornia in Galela Lake, South Galela, North Halmahera - Adiyana Adam (IAIN Ternate, 2020)
South Galela District is one of the districts located in North Halmahera Regency. The sub-district was consist of 7 villages (Seki, Togawa Besi, Togawa, Soakonora, Igobula, Ori, Bale) which are located nearby Lake Galela, overgrown by aquatic vegetation, namely water hyacinth (Eichhornia). The aquatic vegetation has positive and negative impact on the society. The purpose of the study is to determine the South Galela community perceptive on the positive and negative impacts of Eichhornia in Lake Galela. The research used is descriptive quantitative. The population in this study were all residential building plots in Galela Selatan District. Samples were taken randomly on residential building plots. The number of samples is determined using the Slovin formula with a confidence level of 95%, and the number of samples is 300 building parcels. The data collection techniques used are questionnaire, interview, observation, and documentation. The results showed that there are many people in Galela Selatan Subdistrict more dominant in assessing the existence of Eichhornia towards a positive impact, because people saw it support the community's economy, especially making handicrafts. Based on the results of the research, the factors on community perceptions in Galela Selatan District are the level of community knowledge, length of stay of the community, type of work and level of income. These factors have different effects on the level of public perception.Key words: Community Perspective, Eichhornia, Galela Lake